2009
DOI: 10.1111/j.1553-2712.2009.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hospital Admission for Chronic Obstructive Pulmonary Disease Exacerbations in Canadian Emergency Departments

Abstract: Objectives: The objective was to examine predictors of hospital admission among adults presenting to Canadian emergency departments (EDs) for acute exacerbations of chronic obstructive pulmonary disease (COPD). Current acute treatment approaches and outcomes 2 weeks after the ED visit are also described.Methods: Subjects, aged ‡35 years presenting with COPD exacerbations to 16 EDs across Canada, underwent a structured in-ED interview and a telephone interview 2 weeks later.Results: Of 501 study patients, 247 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
1
15
3
Order By: Relevance
“…Some authors from the United States, such as Rowe et al 27 and Tsai et al, 28 reported higher admission rates (49.3 and 62%, respectively) than we did. The differences observed are most likely attributable to our cohort originating from primary care, where the average severity of the disease is lower.…”
Section: Discussioncontrasting
confidence: 37%
“…Some authors from the United States, such as Rowe et al 27 and Tsai et al, 28 reported higher admission rates (49.3 and 62%, respectively) than we did. The differences observed are most likely attributable to our cohort originating from primary care, where the average severity of the disease is lower.…”
Section: Discussioncontrasting
confidence: 37%
“…These have found higher odds of ED admission for age, 66,67 various markers of COPD severity and respiratory distress, 67,68 comorbidity and lower levels of social support, but not sex, although Vidal et al 68 did not retain comorbidity or social support in their final model. We also found effects of older age (although Vidal et al 68 did not, perhaps because of their detailed physiological variables) and comorbidity for the COPD group.…”
Section: Discussion Of Methods and Findingsmentioning
confidence: 99%
“…In 16 EDs across Canada, 49% of 501 patients with acute exacerbations of COPD who were interviewed had been admitted. 67 In a Spanish cohort also covering 16 EDs, 62% of patients were admitted on arrival for a COPD exacerbation. 68 For our two cohorts, approximately three in four ED visits for any reason within 30 days resulted in admission.…”
mentioning
confidence: 99%
“…With respect to progression to respiratory failure, select physiologic parameters such as arterial pH and Glasgow coma scale may indicate which subjects are likely to require endotracheal intubation [13][14][15]. Finally, for determining who requires hospitalizations, Rowe et al [16] observed that approximately half of those AECOPD presenting to the ED required hospitalization. Independent factors associated with need for admission included having ever required systemic corticosteroid therapy and being more severely ill [16].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, for determining who requires hospitalizations, Rowe et al [16] observed that approximately half of those AECOPD presenting to the ED required hospitalization. Independent factors associated with need for admission included having ever required systemic corticosteroid therapy and being more severely ill [16]. Unfortunately, none of these investigations addressing issues ranging from mortality to need for hospitalization have created risk stratification tools for use in the management of AECOPD.…”
Section: Discussionmentioning
confidence: 98%